Portal Hypertensive Biliopathy: An Infrequent Cause of Biliary Obstruction - Cardoso,Ricardo (2015)
Introduction: Biliary obstruction is usually caused by choledocholithiasis. However, in some circumstances, alternative or concurring unusual ethiologies such as portal hypertensive biliopathy (PHB) must be considered. Clinical case: We present the case of a 36-year-old female complaining of jaundice and pruritus. Liver function tests were compatible with biliary obstruction and the ultrasound scan of the abdomen showed dilatation of the intrahepatic biliary ducts, a dilated common bile duct (CBD) and biliary calculi. The computed tomography of the abdomen revealed a portal cavernoma encasing the CBD. Discussion: Portal cavernoma, the hallmark of extrahepatic portal venous obstruction, can cause PHB. When symptomatic, chronic cholestasis is present if a dominant stricture exists whereas biliary pain and acute cholangitis occur when choledocholithiasis prevails. Management must be individualized and usually includes endoscopic therapy to address choledocholithiasis and shunt surgery for definitive treatment.